2005
DOI: 10.2527/2005.834890x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of marbling and shear force on consumers' willingness to pay for beef strip loin steaks

Abstract: Experimental economic procedures were used to measure the effects of changes in marbling score and Warner-Bratzler shear force (WBSF) value on consumer purchasing behavior and willingness to pay for beef strip loin steaks (n = 541). Consumers were more likely to bid on a steak during the experimental auction if the steak had a high marbling score or low WBSF value. Averaging across all consumers in the study (n = 489), the predicted odds that consumers would submit a nonzero bid were favorable for steaks with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(85 citation statements)
references
References 7 publications
1
80
1
3
Order By: Relevance
“…(4) Platter et al (2005) concluded that the prices consumers were willing to pay to purchase steaks increased as marbling increased, and increased as Warner-Bratzler shear force values decreased; consumers in that study were likely to purchase steaks if they had marbling scores of MT 50 or higher, or Warner-Bratzler shear force values of 3.9 kg or lower.…”
Section: Palatability Prediction Using Usda Quality Gradesmentioning
confidence: 99%
See 2 more Smart Citations
“…(4) Platter et al (2005) concluded that the prices consumers were willing to pay to purchase steaks increased as marbling increased, and increased as Warner-Bratzler shear force values decreased; consumers in that study were likely to purchase steaks if they had marbling scores of MT 50 or higher, or Warner-Bratzler shear force values of 3.9 kg or lower.…”
Section: Palatability Prediction Using Usda Quality Gradesmentioning
confidence: 99%
“…Platter et al (2003b) reported that: (i) marbling score displayed a significant relationship to acceptance of steaks by consumers; and (ii) the shape of the predicted probability curve for steak acceptance was approximately linear over the entire range of marbling scores (TR 67 to SA 97 ), suggesting that the likelihood of consumer acceptance of steaks increases~10% for each full marbling score increase between SL and SA. Platter et al (2005) used an experimental auction technique to determine consumer purchasing behaviour and willingness to pay for beef strip loin steaks and determined that: (i) prime steaks received a US$2.47/kg premium and upper two-thirds choice received a US$0.89/kg premium over the mean bid price for select steaks; and (ii) mean bid prices for steaks decreased by US$1.02/kg for each 1 kg increase in shear force value, with 'very tender' steaks receiving bid premiums of US$0.83/kg, US$2.09/kg and US$2.55/kg compared with 'slightly tender,' slightly tough' and 'very tough' steaks.…”
Section: Palatability Prediction Using Usda Quality Gradesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tenderness has repeatedly been cited as the most important element for both eating quality and consumer purchasing decisions (Miller et al 2001;Platter et al 2005) and is a high priority for research in the meat industry (Boleman et al 1998;McKenna et al 2002;Garcia et al 2008). The mechanism of meat tenderisation is a well understood subject.…”
Section: Introductionmentioning
confidence: 99%
“…, tenderness (Feldkamp, Schroeder, and Lusk 2005, Feuz et al 2004, Lusk et al 2001, Platter et al 2005, packaging (Menkhaus et al 1992, Harrison, Harstad, andRutstrom 2004), labeling (Loureiro and McCluskey 2000, Lusk and Fox 2002, Loureiro and Umberger 2003, organic production (Boland and Schroeder 2002), and multiple attributes and attribute bundles (Alfnes and Rickertsen 2003, Lusk, Roosen, and Fox 2003, Tonsor et al 2005, Loureiro and Umberger 2007, Parcell and Schroeder 2007, Ward, Lusk, and Dutton 2008, Martinez 2008, Froehlich, Carlberg, and Ward 2009, Hanagriff, Rhoades, and Wilmeth 2009, Abidoye et al 2011. Several of these studies paid special attention to the issue of retail beef product branding, recognizing its importance for product differentiation and for providing purchase cues to consumers.…”
mentioning
confidence: 99%